Clinical novel exploration of intractable fever in stroke rehabilitation: a single-center cross-sectional retrospective study - Huang Jingjie; Wu Bangqi; Qin Peng; Zhang Ziyi; Cheng Yupei; Wang Chaoran; Chen Yuyan; Bai Jing (Scientific Reports)
Abstract Fever has long been recognized as one of the earliest clinical indicators of illness and remains a leading reason for seeking medical care worldwide. It is typically classified based on its duration and underlying etiology. In clinical settings, intractable fever is as common as acute fever, particularly in patients with brain injuries. Beyond infectious causes, stroke survivors often experience recurrent intractable fever due to central or neurogenic mechanisms. This study aims to retrospectively investigate the incidence and clinical characteristics of acute and intractable fever in patients undergoing stroke rehabilitation. It explores the associations between these characteristics and the different types of fever. Additionally, the study seeks to identify potential risk factors contributing to the development of intractable fever, aiming to guide clinical management and optimize treatment strategies for stroke-related fever. This study evaluated 1,065 stroke patients in the rehabilitation phase who were admitted to the Neurorehabilitation Center between January 1, 2023, and December 31, 2023. Of these, 230 febrile patients met the inclusion criteria and were included in the analysis, comprising 194 cases of acute fever and 36 cases of intractable fever. Medical records and clinical characteristics were collected, and the data from the two groups of febrile patients were analyzed using t-tests, Mann-Whitney U tests, and chi-square tests. Logistic regression analysis was performed to identify risk factors associated with intractable fever, while receiver operating characteristic (ROC) curves were used to assess the predictive performance of individual and combined risk factors. A p-value of less than 0.05 was considered statistically significant. 15.7% of patients experienced intractable fever, which was significantly associated with brainstem lesions (P < 0.05). Compared to patients with acute fever, those with intractable fever had higher NIHSS scores (33.3% vs. 15.5%, P < 0.05), a greater incidence of consciousness disorders (66.7% vs. 28.9%, P < 0.05), and a higher rate of tracheostomy (55.6% vs. 15.5%, P < 0.05). All patients received antibiotic treatment, and gabapentin was administered to 16 cases. Patients with brainstem lesions were less likely to be treated with gabapentin (37.5% vs. 90%, P < 0.05), while those with intracerebral hemorrhage were more likely to receive gabapentin (87.5% vs. 10%, P < 0.05). Logistic regression analysis revealed that consciousness disorders and tracheostomy status were significant risk factors for intractable fever (P = 0.047, OR 6.691, 95% CI 1.030–43.478; P = 0.021, OR 5.366, 95% CI 1.282–22.465). Brainstem lesions also significantly increased the risk (P = 0.002, OR 9.617, 95% CI 2.277–40.614). Although limited in scope, this retrospective study highlights the increased risk of intractable fever during stroke rehabilitation among patients with consciousness disorders, tracheostomy, and brainstem injuries. The key risk factors identified include higher NIHSS scores, impaired consciousness, tracheostomy status, and brainstem lesions.